(untitled) - Welfield, John (London, 1988)
This book examines Japanese politics and diplomacy during the years extending from the disintegration of the Greater East Asia Co-prosperity Sphere in 1944 - 45, through the occupation and the Cold War until the collapse of the American-Soviet detente in 1978.
Keywords: Japan,Japan,World politics,United states; Foreign relations,Foreign relations,Foreign relations; 1945-1989,1945-; United states,Japan